Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Answer:
x = -2/5
x = 1
Step-by-step explanation:
5x² - 3x - 2 = 0
(5x + 2)(x - 1) = 0
⇒ 5x + 2 = 0
⇒ 5x = -2
⇒ x = -2/5
⇒ x - 1 = 0
⇒ x = 1
Answer:
[tex]5 {x}^{2} - 3x - 2 = 0 \\ 5 {x}^{2} - 5x + 2x - 2 = 0 \\ 5x(x - 1) + 2(x - 1) = 0 \\ (x - 1)(5x + 2) = 0 \\ x = 1 \: and \: \frac{( - 2)}{5} [/tex]
- x = 1 and (-2/5) is the right answer.
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.